Etude du pouvoir antibactérien d’Artemisia herba alba « CHIH » - KHEDDOUM, Naima Loudjaine (My University, 2018)
White mugwort "Artemisia herba alba" is an aromatic medicinal plant that has been used for a long time in traditional Algerian medicine. This is the most famous sagebrush in Algeria (CHIH), it is very abundant on the High Plateaux. Biologically, the essential oil of sagebrush leaves examined was active against the two microorganisms tested, namely: Escherichia coli, Staphylococcus aureus. This study has shown that the essential oil tested has an interesting antimicrobial activity against the two extracts obtained by maceration of the stems and leaves do not mark any activity. Overall, the results are promising and open up new perspectives in the field of natural applications that can be a valid alternative to replace chemicals. In the end, if white sagebrush is considered a material full of medicinal and nutritional substances (fodder plant), it is also a source of substances (essential oil) that have remarkable biological effects.
Keywords: Antimicrobial activity; Biological activity; White wormwood; Essential oil; Activité antimicrobienne; Activité biologique; Armoise blanche; Huile essentielle